Global, regional, and national burden of laryngeal cancer in middle-aged and older adults from 1990 to 2021: an analysis of age and sex differences and attributable risk factors - Hongxia Xiao; Hui Wang; Hui Zhang; Shanying Wu; Bo Yu (Frontiers in Public Health)
BackgroundLaryngeal cancer (LC) is a prevalent head and neck tumor, yet few studies quantify its disease burden and trends in risk factors of the age subgroup of middle-aged and older adult people (MAOP).MethodsBased on Global Burden of Disease 2021 (GBD 2021) data, this study comprehensively assessed trends of disease burden in the age subgroup of LC in MAOP across 204 countries and regions from 1990 to 2021, covering incidence, prevalence, mortality, and disability-adjusted life years (DALYs). The estimated annual percentage change (EAPC) and joinpoint regression model were used to analyze the trends of disease burden and the changes in disease burden attributed to tobacco, alcohol, and occupational risk factors.ResultsWorldwide, the number of LC in MAOP prevalence, incidence, mortality, and DALYs totaled 887,500, 163,300, 97,500, and 2,284,800 in 2021. Over the previous 32 years, the rates of these indicators declined, with EAPC of −0.62 (−0.69 to −0.55), −0.95 (−1.04 to −1.87), −1.52 (−1.6 to −1.43), and −1.69 (−1.79 to −1.59), respectively. Regions with high Sociodemographic Index (SDI) showed high prevalence and morbidity. Still, they had low mortality and DALY rates, whereas areas with low SDI, such as Sub-Saharan Africa, experienced high mortality and DALY rates. Central Europe, a high-middle SDI region, was a “hotspot” for laryngeal cancer. Before the age of 75, males showed a more significant burden of disease indicators, with a peak incidence rate of 28.05 (23.93, 30.47) per 100,000 individuals between the ages of 85 and 90. However, the 85–89 and 90–94 age groups saw rising prevalence rates. The main risk factor for LC-related deaths and DALY in MAOP was tobacco exposure, particularly in low-middle SDI regions.ConclusionIn the last 32 years, the burden of LC in MAOP has declined globally, yet age-related disparities and SDI stratification persist. Men aged before 75 and after 85 need to be targeted as key groups for prevention and control. Tobacco exposure was the leading risk factor, especially in low-middle SDI regions. These findings highlight the critical necessity for tailored public health strategies and policies.